Mountain Rain - Crossman, Eileen Fraser; Nang ChanYeema (Singapore Overseas Missionary Fellowship, 2008)
The life story of James Fraser a missionary who spent most of his life bringing Christ to the Lisu tribespeople of Yunnan China.
Keywords: Biography